Keeping in Step with the Spirit (Gal 5:25): Godliness as Evidence of God’s Abiding Presence - Bitrus A. Sarma (Conspectus)
There is a growing interest in the person and work of the Holy Spirit in African Christianity. However, although most Christians will agree that the presence of the Holy Spirit in the church is indispensable, the signs of such presence are disputed. A common assumption or fallacy among some believers is that the display of supernatural spiritual gifts is sufficient and a tangible indicator of the Spirit’s presence. While Galatians 5:22–25 and other Pauline texts reveal that godliness is central in the Christian life, it is often trivialized and under-pursued. The premise of this paper is that godliness (e.g., the fruit of the Spirit), is a perceptible indicator of his abiding presence. The purpose of the paper is twofold: the first is to contribute to the ongoing discussion regarding the person and work of the Holy Spirit in the academic community. The second is to stress the significance of cultivating a godly character worthy of our calling, and so keeping in step with the Spirit (Gal 5:25). The approach of the paper is inductive, theological, and contextual. The aim is to delineate the theological and ethical implications of the fruit of the Spirit in the context of Christian life and ministry.